2002
DOI: 10.1074/jbc.m110936200
|View full text |Cite
|
Sign up to set email alerts
|

A Calcium/Calmodulin-dependent Activation of ERK1/2 Mediates JunD Phosphorylation and Induction of nur77 and20α-hsd Genes by Prostaglandin F2α in Ovarian Cells

Abstract: We have previously demonstrated that prostaglandin F 2␣ (PGF 2␣ ) induces a rapid and transient expression of Nur77 in luteal cells. We have shown that Nur77 plays an important role in ovarian physiology by mediating the PGF 2␣ induction of 20␣-HSD, a steroidogenic enzyme involved in the catabolism of progesterone. In this report we established, using luteinized granulosa cells, that PGF 2␣ stimulates in vitro nur77 expression in a time-and dose-dependent manner. Serial 5-deletion of the nur77 promoter reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 49 publications
4
73
1
1
Order By: Relevance
“…We confirmed that JunD specifically binds to NAP4 and is activated indirectly by PKC through phosphorylation of JunD by MAP kinases (JNK and ERK) ( Figure 5). In ovarian cells, calcium-dependent activation of ERK mediates JunD phosphorylation and Nur77 induction by prostaglandin (Stocco et al, 2002). In this case, JunD induces the Nur77 through NAP1 and NAP2 elements.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that JunD specifically binds to NAP4 and is activated indirectly by PKC through phosphorylation of JunD by MAP kinases (JNK and ERK) ( Figure 5). In ovarian cells, calcium-dependent activation of ERK mediates JunD phosphorylation and Nur77 induction by prostaglandin (Stocco et al, 2002). In this case, JunD induces the Nur77 through NAP1 and NAP2 elements.…”
Section: Discussionmentioning
confidence: 99%
“…14,20 JunD is phosphorylated at Ser100 in activated HSCs and is necessary for stimulation of TIMP-1 gene transcription. We propose that Ser100 phosphorylated JunD homodimers operate in concert with either RUNX1A or RUNX2 to generate high-level TIMP-1 expression by activated HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The Ser100 of JunD is also an efficient target for phosphorylation by ERK1/2. 14,20 Treatment of rat HSCs with the ERK1/2 inhibitor PD98059 resulted in 40% repression of TIMP-1 promoter activity but had no effect on promoter activity in 3T3 cells (Fig. 7C).…”
Section: Serine Phosphorylation Of Jund Is Required For Transactivatimentioning
confidence: 99%
See 2 more Smart Citations